Do Capital Intensity and Profitability Affect Tax Avoidance in Manufactuting Company in Indonesia? - Tirta Budi Kusuma; Friska Firnanti (STIE Malangkucecwara, 2023)
Purpose: The objective of this research is to obtain empirical evidence about the influence of capital intensity, profitability, leverage, company size, sales growth, independent commissioner, and fiscal loss compensation, as independent variables to tax avoidance as dependent variable in Indonesian manufacturing companies. Methodology (for empirical paper): This research employed multiple regression methodology for data analysis. There are 56 companies listed in manufacturing sectors in Indonesia Stock Exchange on 2016-2018 that meet the criteria by using purposive sampling method. Result: The result indicates that capital intensity and profitability have effects to tax avoidance, while other independent variables such as leverage, company size, sales growth, independent commissioner, and fiscal loss compensation have no effect to tax avoidance practice in the company. Originality: This paper contributes to showing how the economic capacity of companies can affect the reluctance of companies to pay taxes. Implication: The action of tax avoidance is beneficial for the company because the company will pay a smaller tax burden. However, this action causes losses for the government in tax collection.